1988
DOI: 10.2307/1943178
|View full text |Cite
|
Sign up to set email alerts
|

Latitudinal Variation in Reproductive Timing of a Short‐Lived Monocarp, Daucus Carota (Apiaceae)

Abstract: A reciprocal transplant experiment was conducted to examine several aspects of life—history variation in Daucus carota along its latitudinal range in eastern North America. Seeds collected from natural populations at 36°, 42°, and 45° N were sown onto plots at each of the three latitudes. Marked seedlings were followed for 3 yr to examine (1) genetic and environmental components of variation in growth, survival, and year of reproduction; (2) size and age at time of reproduction; and (3) the roles that density—… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
81
0
1

Year Published

1993
1993
2020
2020

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 109 publications
(91 citation statements)
references
References 38 publications
9
81
0
1
Order By: Relevance
“…The establishment of clines is a feature of many species invasions and has been interpreted as a hallmark example of adaptive evolution in action (Johnston & Selander, 1964;Lacey, 1988;Weber & Schmid, 1998;Huey et al, 2000;Kollmann & Banuelos, 2004;Maron et al, 2004Maron et al, , 2007Leger & Rice, 2007;Etterson et al, 2008;Montague et al, 2008). In our study, divergence was often observed in excess of the neutral expectation generated by ancestry, offering particularly strong evidence that the clines are adaptive.…”
Section: Climate Adaptation Of Silene In Europe and North Americasupporting
confidence: 58%
“…The establishment of clines is a feature of many species invasions and has been interpreted as a hallmark example of adaptive evolution in action (Johnston & Selander, 1964;Lacey, 1988;Weber & Schmid, 1998;Huey et al, 2000;Kollmann & Banuelos, 2004;Maron et al, 2004Maron et al, , 2007Leger & Rice, 2007;Etterson et al, 2008;Montague et al, 2008). In our study, divergence was often observed in excess of the neutral expectation generated by ancestry, offering particularly strong evidence that the clines are adaptive.…”
Section: Climate Adaptation Of Silene In Europe and North Americasupporting
confidence: 58%
“…For example, seed used in Denmark is produced in regions with a warmer climate, such as Southern Europe, California, Chile and Australia. From their wild southern fathers, the hybrids inherit a potential for flowering in their first year (annuality) (Lacey, 1988;Hauser and Bj rn, 2001), and they therefore often flower (bolt) in root-crop fields if not weeded away. From these plants, pollen and seeds may disperse into neighbouring wild populations.…”
Section: Introductionmentioning
confidence: 99%
“…For perennials, ecotypic variation in reproductive schedules, growth, and longevity has been documented in Plantago lanceolata (van Groenendael 1985) and Daucus carota (Lacey 1988). Yet, even though variation within populations is most relevant to selection, studies of genetic differences in the timing and consequences of reproduction in perennial plants are lacking at the population scale.…”
mentioning
confidence: 99%